Activity of an antimicrobial hydrocephalus shunt catheter against Propionibacterium acnes - Bayston, Roger; Vera, Litza; Ashraf, Waheed (American Society for Microbiology, 2010)
Shunt infection is a major complication affecting approximately 10% of procedures. Propionibacterium acnes, an anaerobic skin bacterium, is increasingly recognized as a shunt pathogen, causing up to 14% of infections. Though susceptible to penicillin and cephalosporins, P. acnes shunt infections are not preventable by means of perioperative prophylaxis, due to poor cerebrospinal fluid penetration. Antimicrobial shunts with activity against staphylococci are available, but their activity against P. acnes is unknown, and the study was designed to determine this. Three methods of evaluation were used in order to determine the emergence of resistance when exposure is to high inocula for long periods, the time taken to kill 100% of the bacteria attached to the shunt, and the duration of activity under constant flow conditions with repeated bacterial challenge. Despite repeated exposure to high bacterial inocula over 70 days, no resistance was seen. The time taken to kill all attached bacteria, 96 h, was twice that taken to kill attached staphylococci. Nevertheless, under constant flow conditions with repeated challenges, the antimicrobial catheters resisted colonization by P. acnes for 56 days. Using tests that were designed to be clinically predictive when done together, the results suggest that the antimicrobial catheters will be able to prevent colonization of hydrocephalus shunts by P. acnes.